COVID-19 in long-term care facilities in Brazil: serological survey in a post-outbreak setting - Barros, Eliana Nogueira Castro de; Valle, Adriana P. do [UNESP]; Braga, Patricia Emilia; Viscondi, Juliana Y. K.; Fonseca, Antonio R. B. da [UNESP]; Vanni, Tazio; Silva, Anderson da; Cardoso, Maria Regina; Villas-Boas, Paulo Jose F. [UNESP]; Precioso, Alexander Roberto (Inst Medicina Tropical Sao Paulo, 2021)
This cross-sectional seroepidemiological survey presents the seroprevalence of SARS-CoV-2 in a population living in 15 Long-Term Care Facilities (LTCFs). after two intra-institutional outbreaks of COVID-19 in the city of Botucatu, Sao Paulo State, Brazil. Residents were invited to participate in the serological survey performed in June and July 2020. Sociodemographic and clinical characterization of the participants as well as the LTCF profile were recorded. Blood samples were collected, processed and serum samples were tested using the rapid One Step COVID-19 immunochromatography test to detect IgM and IgG anti-SARS-CoV-2. Among 209 residents, the median of age was 81 years old, 135 (64.6%) were female and 171 (81.8%) self-referred as being white. An overall seroprevalence of 11.5% (95% CI: 7.5% - 16.6%) was found. The highest seroprevalences of 100% and 76.9% were observed in LTCFs that had experienced COVID-19 outbreaks. Most residents with positive immunochromatography tests (70.8%) referred previous contact with a confirmed COVID-19 case. Although there was a relatively low seroprevalence of COVID-19 in the total number of elderly people, this population is highly vulnerable and LTCFs are environments at higher risk for COVID-19 dissemination. A well-established test for COVID-19 policies, the adequate characterization of the level of interaction between residents and the healthcare provider team and the level of complexity of care are crucial to monitor and control the transmission of SARS-CoV-2 in these institutions.
Keywords: COVID-19; SARS-CoV-2; Seroprevalence; Long-term care facility; Elderly